Sigorta Hukukunda abonman sözleşmesi ve hükümleri - Satici, İbrahim Uğur (Hasan Kalyoncu Üniversitesi, 2020)
Türk Ticaret Kanununda mevcut olmayan abonman sözleşmesi yük sigorta sözleşmelerinin ileride yapılmasını sağlama bakımından uygulama ve teoride önem arz etmektedir. Abonman sözleşmesiyle birlikte taraflar genel biçimde belirledikleri menfaat kapsamına girecek yüklerin ileride sigorta sözleşmelerinin yapılmasını sağlayabilmektedir. Bu sözleşmenin TTK.? da düzenlenmemesi nedeniyle uygulanacak hükümlerin tespiti için hukuki niteliğinin tespiti önem arz etmektedir. Doktrinde ileri sürülmüş görüşler ayrı ayrı değerlendirilerek karar verilen hukuki niteliği sayesinde uygulanacak hükümler belirlenebilmektedir. Bu sayede bu sözleşmenin nasıl kurulacağı, tarafları ve taraflar için doğurduğu hükümler veya genel ya da özel şartlara yönelik bir uyuşmazlık çıktığında sorunun giderilmesi kolaylaşmaktadır.

The subscription contract, which does not exist in the Turkish Commercial Code, is important in practice and theory in terms of ensuring the future execution of freight insurance contracts. With the subscription agreement, the parties can ensure that the cargoes that will fall within the scope of the benefit they have determined in general are signed in the future. Since this contract is not regulated in the TCC, it is important to determine the legal nature for determining the provisions to be applied. The opinions put forward in the doctrine are evaluated separately and the provisions to be applied can be determined thanks to the legal nature of the decision. In this way, it becomes easier to resolve the problem when there is a dispute regarding the establishment of this contract, the provisions it creates for the parties and the parties, or the general or special conditions.
Floating policy and its provisions in Insurance Law
Keywords: Hukuk; Law